Peningkatan pengetahuan “Pentingnya personal hygiene organ reproduksi wanita serta praktik penerapannya” pada ibu dan remaja putri di Kelurahan Mojo Surabaya - Purbowati, Rini; Tri Ratnasari , Diana; Soekanto, Ayly; Tjandra, Lusiani; Masfufatun, Masfufatun; Indahsari, Noer Kumala (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Infectious and deadly diseases caused by bacterial infection are currently still a global problem, one of which is Bacterial Vaginosis (BV) infection. Following polymicrobial as a result of changes in normal hydrogen peroxide produced by Lactobacillus spp in the vagina. One of the triggering factors for BV is the practice of "Douching" or washing the vagina regularly due to a lack of public knowledge about how to perform and maintain the cleanliness of the reproductive system in a good and correct way. form of participation can be in the form of Community Service Activities by providing correct education following with their expertise. The purpose of this activity is to increase the knowledge and abilities of mothers and young women in Mojo Village, Surabaya in particular, and the community in general about the Importance of Personal Hygiene of Women's Reproductive Organs and their Application Practices. This service activity was carried out on Sunday, October 9, 2022, at the RW 5 Mojo hall, attended by 50 participants, carried out using 2 methods, namely the lecture method with the material in the form of powerpoints with the title "Recognizing and Maintaining Women's Reproductive Health" and the practice method "the method of using hand wipes". good and right”, which was preceded by a simulation video showing the distribution of goody bags (containing feminine products) and leaflets. Measurement of the increase in participants' knowledge was carried out through pretest and post-test. The measurement results showed that the average pretest value of participants was 71.9 ± 17.1 and the average post-test value of participants was 86.71 ± 10.7 so the delta value (change in score) was 14.81.